Rational design of FRET sensor proteins based on mutually exclusive domain interactions - Merkx, Maarten (2013)
Proteins that switch between distinct conformational states are ideal to monitor and control molecular processes within the complexity of biological systems. Inspired by the modular architecture of natural signaling proteins, our group explores generic design strategies for the construction of FRET-based sensor proteins and other protein switches. Here I show that designing FRET sensors based on mutually exclusive domain interactions provides a robust method to engineer sensors with predictable properties and an inherently large change in emission ratio. The modularity of this approach should make it easily transferable to other applications of protein switches in fields ranging from synthetic biology, optogenetics and molecular diagnostics.